2016
DOI: 10.1371/journal.pone.0158721
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temporal and Spatial Predictions on Stretch Reflexes of Ankle Flexor and Extensor Muscles While Standing

Abstract: The purpose of the present study was to investigate how stretch reflex (SR) responses in the ankle extensor (soleus: SOL) and flexor (tibialis anterior: TA) muscles would be modulated with temporal and/or spatial predictions of external perturbations and whether their effects are specific to the standing posture. SR responses in the SOL/TA were elicited by imposing quick ankle toes-up/toes-down rotations while standing upright and in the supine position. We designed four experimental conditions based on pre-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
1
24
1
4
Order By: Relevance
“…Our present analyses demonstrated that the corticospinal excitability in the TA was enhanced when the timing cue was given. This result is inconsistent with previous studies of the stretch reflex that reported the reduced amplitude of the long-latency response ( Nakazawa et al, 2009 ; Fujio et al, 2016 ). We suspect that this discrepancy is due to the difference in perturbation types.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our present analyses demonstrated that the corticospinal excitability in the TA was enhanced when the timing cue was given. This result is inconsistent with previous studies of the stretch reflex that reported the reduced amplitude of the long-latency response ( Nakazawa et al, 2009 ; Fujio et al, 2016 ). We suspect that this discrepancy is due to the difference in perturbation types.…”
Section: Discussioncontrasting
confidence: 99%
“…The long-latency EMG responses of the ankle plantar muscle and dorsiflexor muscle were reported to be enhanced when the posture was unstable ( Christensen et al, 2001 ; Nakazawa et al, 2003 ). It was also demonstrated that the amplitude of these EMG responses was markedly reduced when an advance notification about the timing of perturbation onset was given to the subjects ( Nakazawa et al, 2009 ; Fujio et al, 2016 ). It is thus plausible that the excitability of a corticospinal pathway would be enhanced when a subject can predict that a postural perturbation is to occur, and the enhanced excitability could be reduced when the subject can predict the timing of the perturbation.…”
Section: Introductionmentioning
confidence: 95%
“…Há evidências de que as respostas posturais podem ser moduladas por processamento cognitivo (Fujio, Obata, Kawashima, & Nakazawa, 2016;Mierau, Hulsdunker, & Struder, 2015;Smith, Jacobs, & Horak, 2012, 2014Varghese et al, 2014). Essas evidências sugerem que várias regiões corticais e subcorticais, tais como as áreas frontais, o córtex cingulado anterior, área pré-motora, cerebelo e gânglios da base estão relacionados com processos atencionais e de preparação motora envolvidos com o controle postural.…”
Section: Introductionunclassified
“…Uma questão advinda dessa definição é quais informações de contexto podem ser utilizadas pelo central set para melhorar as respostas posturais automáticas. Essa participação do central set em respostas posturais automáticas tem sido generalizada para diferentes informações do contexto, tais como dicas prévias sobre as características da perturbação postural (Chong, Horak, & Woollacott, 2000;Fujio et al, 2016;Jacobs et al, 2008;Mochizuki et al, 2010;Mochizuki, Sibley, Esposito, Camilleri, & McIlroy, 2008;Silva et al, 2015;Smith et al, 2012Smith et al, , 2014, experiência prévia com a perturbação postural (Horak et al, 1989;Mierau et al, 2015;Papegaaij et al, 2012), restrição imposta por uma tarefa manual realizada concomitantemente à manutenção do equilíbrio postural (de Lima-Pardini et al, 2014;de Lima-Pardini et al, 2012;de Lima, de Azevedo Neto, & Teixeira, 2010), condições posturais iniciais , instrução (Smith et al, 2014) e estado emocional (Maki & McIlroy, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation